Investigation of Allium Sativum L.(GARLIC) as an alternative source for glutathione and cysteine production - Mohd. Salleh, Hamzah (s.n, 2013)
Production of glutathione and cysteine can be achieved through several methods such as chemical synthesis, enzymatic catalysis, microbial fermentation, and genetic/metabolic engineering. At present, glutathione and cysteine are commonly being sourced from animal keratin or hair, which imposed ethical and halal-haram issue. In this study, garlic bulbs were extracted using ultrasonic-assisted water extraction based on One Factor at a Time (OFAT)experimental design